Effect of percutaneous stenting strategy of unresectable malignant hilar biliary obstruction by three‐dimensional reconstruction volumetry - Xiaobo Fu; Weiwei Jiang; Maoyuan Mu; Guobao Wang; Han Qi; Zixiong Chen; Mengxuan Zuo; Fei Gao (Cancer Medicine, 2023)
Abstract Purpose To explore clinical outcomes of percutaneous stent implantation using volumetric criteria for unresectable malignant hilar biliary obstruction (MHBO). Additionally, aimed to identify the predictors of patients' survival. Methods Seventy‐two patients who were initially diagnosed with MHBO between January 2013 to December 2019 in our center were retrospectively included. Patients were stratified according to the drainage achieved ≥50%, <50% of the total liver volume. Patients were divided into two groups: Group A (≥50% drainage), and Group B (<50% drainage). The main outcomes were evaluated in terms of relief of jaundice, effective drainage rate, and survival. Related factors that affect survival were analyzed. Results 62.5% of the included patients reached effective biliary drainage. The successful drainage rate was significantly higher in Group B than in Group A (p < 0.001). The median overall survival (mOS) of included patients was 6.4 months. Patients who received drainage ≥50% of hepatic volume achieved longer mOS than those who received drainage <50% of hepatic volume (7.6 months vs. 3.9 months, respectively, p = 0. 011). Patients who received effective biliary drainage had longer mOS than those who received ineffective biliary drainage (10.8 months vs. 4.4 months, respectively, p < 0.001). Patients who received anticancer treatment had longer mOS than those who only received palliative therapy (8.7 months vs. 4.6 months, respectively, p = 0.014). In the multivariate analysis, KPS Score ≥ 80 (p = 0.037), ≥50% drainage achieved (p = 0.038), and effective biliary drainage (p = 0.036) were protective prognostic factors that affected patients' survival. Conclusion Drainage achieved ≥50% of the total liver volume by percutaneous transhepatic biliary stenting seemed to have a higher effective drainage rate in MHBO patients. Effective biliary drainage may create chances for these patients to receive anticancer therapies that seem to provide survival benefits.